Cognitive dysfunction is common in middle‐aged adults with type 2 diabetes in South Africa: New insights in determinants of dementia to advance prevention strategies: A view from Latin America and African countries. (7th December 2020) - Bobrow, Kirsten; Kornblith, Erica S; Gouse, Hetta; Robbins, Reuben N; Yaffe, Kristine; Farmer, Andrew J; Levitt, Naomi
Abstract: Background: Type 2 diabetes (T2DM) is a leading, potentially modifiable risk factor for cognitive impairment and dementia. However, very little is known about the burden of cognitive impairment in adults with T2DM in low‐ and middle‐income settings. We describe patterns of cognitive functioning and impairment in adults with T2DM in primary care in Cape Town, South Africa. Methods: Participants were recruited from a final study visit of a randomized control trial study that assessed adherence support for T2DM (ISRCTN7076880) using brief‐messages. Participants completed a standardized neuropsychological test battery previously adapted for use in South Africa that assessed seven cognitive domains: learning (verbal and visual), delayed recall/memory (verbal and visual), working memory, processing speed, executive function, language, and fine motor skills. Linear regression was used to adjust individual raw test scores for age, sex and education. We used the standardized residuals from the models as a standard score and defined impairments as >1 standard deviation below the mean. Logistic regression models were fitted to explore associations between demographics, health behaviors, and glycaemic control and the number of domains impaired (≥2.) Results: Eighty participants (75% women) with a mean age of 55 years (SD=11) and 9.2 (SD=3.4) years of education were enrolled. Mean HbA1c was 83 mmol/mol (SD=1.1) and duration of type 2 diabetes was 8 years (SD=6). Eight participants (11%) had co‐morbid HIV. Impairment was present across all cognitive domains. Proportion impaired varied by domain and test from 5% to 15%. One third of participants were impaired in only one domain, and one third in two or more. Male sex was significantly associated with impairment in two or more domains. Glycemic control, HIV‐status, self‐rated health, mood or premorbid functioning did not significantly predict impairment by type or number of domains impaired. Conclusion: Cognitive impairment is common among middle‐aged adults with T2DM being managed in primary care in South Africa. Further research is required to clarify predictors, and by implication management of cognitive impairment in people with T2DM in low‐and middle‐income settings.